Formative feedback in the clinical practice setting: What are the perceptions of student radiographers?. Issue 1 (February 2016) - Fowler, P.; Wilford, B.
Abstract: The role of feedback to a learner's development has been well established. There is an absence of studies relating to student radiographers experience of gaining and applying formative feedback. This study investigated processes involved in gaining written formative feedback in the clinical practice setting as well as the impact feedback had on student radiographers learning. The data was collected from radiography students at two higher education institutions by electronic questionnaire comprising scaled and open questions. There was a response rate of 37% (n = 103/279). Scaled data was analysed using inferential statistics and the qualitative data helped explain the findings. The majority of students recognised radiographers were frequently busy; resulting in feedback that is generic and not always timely. There is strength of opinion 82.6% (n = 85/103) that student radiographers do not work with any one radiographer consistently enough to enable the provision of constructive and meaningful feedback. There appears to be difficulty in obtaining the comments but the evidence shows they are valued. The majority of students seek feedback that is specific and will clearly identify areas for development. They reflect on feedback as well as use self-criticism of their practice performance indicating the development of autonomous skills. The challenge of enabling consistent one to one working with radiographers, the need to maximise a learning culture within practice environments and ensuring full engagement by radiographers and students could be addressed by modification of the feedback system, a working group being formed from students, supervising radiographers and academic tutors. Highlights: Students value constructive criticism and on-going verbal feedback. Written feedback is not always easy to obtain because of pressures on staff time. Student radiographers are rarely able to work consistently with the same person. Student and mentor discussion of the feedback is important to maximise its value.